A New Scale for Assessing Benzodiazepine Use Motives Among Community and Clinical Samples: The Development and Validation of the MBUQ- 48. - Péter, Lea; Lázár, Bence András; Bajsz, András; Bőthe, Beáta; Paksi, Borbála; Czakó, Andrea; Griffiths, Mark D.; Horváth, Zsolt; Demetrovics, Zsolt; Andó, Bálint (International Journal of Mental Health & Addiction, 2026)
The risk for non-medical use and dependence on benzodiazepines (BZDs) is high. However, there is no available validated psychometric instrument that assesses the motives for BZD use. Therefore, the aim of the present study was to develop a scale identifying the motives for BZD use, examine the factor structure, and corroborate the construct validity of the scale. Items for the scale were generated from previous data collection and from the empirical literature. Consequently, 82 motives were tested among a large community (N = 1424) and a clinical sample (N = 113). Medical and non-medical BZD use, other substance use, and several psychological constructs were assessed in both samples. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), as well as bivariate correlations and regression analyses, were performed. The EFA model included 48 items with four factors: "personal and interpersonal benefits", "substance use regulation", "coping", and "sleep facilitation". The four-factor CFA model demonstrated adequate levels of model fit. Members of the clinical sample had significantly higher rates of all four motives. The construct validity of the Motives for Benzodiazepine Use Questionnaire (MBUQ-48) was supported by positive correlations between the motivational factors and psychological constructs, different outcomes of BZD use, and other substance use. Coping motives had positive association with various outcomes of BZD use. Based on the results, the MBUQ-48 is a reliable and valid scale for assessing motives for BZD use. Exploring the motivations underlying BZD use can help clinicians in the recognition of the risk of BZD use disorder and in increasing the efficacy of therapeutic processes.